2020
DOI: 10.29309/tpmj/2020.27.12.4728
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of internal sphincterotomy versus topical 0.2 % glyceryl trinitrate ointment after hemorrhoidectomy.

Abstract: Objectives: To compare the efficacy of 0.2% glyceryl trinitrate ointment versus internal sphincterotomy after hemorrhoidectomy. Study Design: Randomized Controlled Trial. Setting: Department of Surgery Unit III, at Lahore General Hospital, Lahore. Period: 6 months (August 2017 to February 2018). Material & Methods: The OPD of the Department of Surgery included 124 patients who satisfied the inclusion criteria. There were two groups of patients, Group A and Group B. Group-A was told to use gloved finger thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Pulmonary edema and HELLP syndrome were the most common complications in our study population. It was supported by studies of Zuberi NF et al, 15 Aali BS et al 7 Tufnell DJ et al 16 and Imarengiaye et al 9 Mortality was 8.57% in our study. The studies conducted by Sailaja K et al 10 showed mortality rate of 9.9%, Gupta S et al 12 showed 41.67%, Ozcelik M et al 13 showed 12.5%.…”
Section: Discussionsupporting
confidence: 89%
“…Pulmonary edema and HELLP syndrome were the most common complications in our study population. It was supported by studies of Zuberi NF et al, 15 Aali BS et al 7 Tufnell DJ et al 16 and Imarengiaye et al 9 Mortality was 8.57% in our study. The studies conducted by Sailaja K et al 10 showed mortality rate of 9.9%, Gupta S et al 12 showed 41.67%, Ozcelik M et al 13 showed 12.5%.…”
Section: Discussionsupporting
confidence: 89%
“…The use ofglyceryltrinitrate ointment (GTN) which is a vasodilator has been linked with relaxing anal canals smooth muscle and also decrease the sphincter spasm production [8][9] . This results in reversal of chemical sphincterotomy.…”
Section: Introductionmentioning
confidence: 99%